2005
DOI: 10.4049/jimmunol.174.2.735
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antigen-Capturing Cells as Basophils

Abstract: Binding of intact Ag is a hallmark of Ag-specific B cells. Apart from B cells, a small number of non-B cells can bind Ag with comparable efficacy as B cells and are found in the peripheral blood, spleen, and bone marrow of mice. This population has been observed for a long time and recently named “Ag-capturing cells.” Their identity remained enigmatic. In this study, we show that these cells are basophilic granulocytes. Their ability to capture Ags is dependent on surface IgE receptors and on Ag-specific plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…[19][20][21] Furthermore, CCR2 is also expressed on endothelial cells during inflammation, consistent with a potential role in wound repair. 22 Information regarding the expression of CCR2 on non-hematopoietic cells in the CNS is currently limited and inconsistent.…”
Section: Expression Of Ccr2mentioning
confidence: 77%
“…[19][20][21] Furthermore, CCR2 is also expressed on endothelial cells during inflammation, consistent with a potential role in wound repair. 22 Information regarding the expression of CCR2 on non-hematopoietic cells in the CNS is currently limited and inconsistent.…”
Section: Expression Of Ccr2mentioning
confidence: 77%
“…It has been thought that basophils are predominant Ag-capturing cells (41), and that Ag and Ag-specific IgE complexes activate basophils to produce IL-4 and IL-6, leading to enhanced humoral memory immune responses (7). However, a recent report showed that basophil-deficient mice still have efficient humoral immune responses (14).…”
Section: Discussionmentioning
confidence: 92%
“…During secondary Ag exposure, Ag-specific, IgE-bearing basophils capture Ag, become activated, and secrete cytokines, which subsequently facilitates memory B cell responses (7,41). Although WT and Sema4B 2/2 basophils produced comparable levels of IL-4 and IL-6 on FcεRI cross-linking (Supplemental Fig.…”
Section: /2 Mice Have Enhanced Ige Memory Responsesmentioning
confidence: 99%
“…Bovine type II collagen (Sigma C1188; St. Louis, MO) was dissolved overnight in 0.1M acetic acid at a concentration of 2 mg/ml and, for the first injection, was emulsified in an equal volume of Freund's complete adjuvant. Male DBA/1 mice were immunized with an intra-/subcutaneous injection of 100 l emulsion at the base of the tail on day 0, and an intraperitoneal (IP) injection of 100 g type II collagen without adjuvant at day 21 Histology. Hind paws were fixed in 3.7% formalin for 24 hours, washed in PBS, and decalcified with RDO rapid decalcifier (Medite, Burgdorf, Germany).…”
Section: Methodsmentioning
confidence: 99%